Emerging stock markets factbook 1998 - International Finance Corporation; World Bank. (Washington, D.C. : International Finance Corporation, 1998)
This factbook tracks the development of equity markets in developing countries.
aia 09/09/2016
Ref
Keywords: Stock exchanges; Fact book - stock; Developing countries